PERANCANGAN PERANGKAT LUNAK SISTEM ABSENSI DENGAN BARCODE CARD PADA FAKULTAS ILMU KOMPUTER UNIVERSITAS METHODIST INDONESIA - Darwis Robinson Manalu; Harlen Gilbert Simanullang (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2015)
Faculty of Computer Science is one of the faculties at the University Methodist Indonesia. At this school there is a sistemabsensi faculty and students who are still running it manually, which dalampenerapan attendance system, there are some things that become obstacles, which include the effectiveness and efficiency of time and prosespengabsenan. With the above reasons, the authors try to memberikanalternatif solving problems by creating a software absensiyang system will record data and a list of faculty and student attendance, number and recapitulation presence of faculty and students, which will be made in a systematic and computerized WITH barcode, which will eliminate the process attendance of lecturers and students who have been running it manually in the Faculty of Computer Science. Barcode will method of reducing levels of fraud at the time of charging absent students, and to improve discipline in attendance. At this writing will also be explained stages of processing, mulaidari process of analysis, planning, design by using VB.Net and MySQL for its database, to manufacture DFD (Data Flow Diagram) as an indication of the current procedure that akanditerapkan data on the system, and the analysis of inputs and output, to know anything what the data will be input and output.